The effect of hygromycin B quality towards candida albicans susceptibility - Engku Nasrullah Satiman, Engku Anis Fariha; Kaderi, Mohd Arifin; Ramzi, Ahmad Bazli; Arzmi, Mohd Hafiz (2021)
Candida albicans is a medically important opportunistic pathogen that can be found in oral cavity. It is greatly associates in mono- and polymicrobial biofilms development with other oral microorganisms. However, aberrant ploidy number and unusual codon usage in C. albicans complicate its genetic editing process. Hygromycin B is an antifungal that is useful for a selective marker in C. albicans genetic transformation. Specialised codon-optimized hygromycin resistance gene (CaHygB) derived from plasmid pYM70 enables C. albicans transformants to grow on a selective plate containing hygromycin B. The objective of the study is to determine the effect of hygromycin B quality in the detection of C. albicans gene transformation with the hypothesis that the performance of two different qualities is similar during the selection of C. albicans transformants on YPD-hygromycin B agar plate. C. albicans ATCC MYA-4901 was revived and grown on YPD agar for 48 hours at 37°C. Meanwhile, glycerol stock of E. coli carrying pYM70 was revived on LB-ampicillin agar at 37°C for overnight. Plasmid pYM70 was later extracted and used in the subsequent transformation of C. albicans. The competent cell of C. albicans was prepared using the modified lithium-acetate method. Plasmid pYM70 was transformed into the competent cells of C. albicans using the electroporation method. The transformed cells were sub-cultured on YPD agar containing 600 μg/ml hygromycin B from two brands. The growth of transformants was observed after three to four days of incubation at 37°C in a dark environment. Our study showed a successful transformation of C. albicans with pYM70, which exhibited resistance towards both hygromycin B (Gb and Bb). However, wild-type and empty competent cells (negative controls) exhibited resistance towards hygromycin B Bb. In conclusion, different qualities of hygromycin B affect the susceptibility of C. albicans which may lead to a false result during C. albicans transformation.